Cognitive impairment in Parkinson's disease: Association between patient-reported and clinically measured outcomes. (December 2016) - Mills, Kelly A.; Mari, Zoltan; Pontone, Gregory M.; Pantelyat, Alexander; Zhang, Angela; Yoritomo, Nadine; Powers, Emma; Brandt, Jason; Dawson, Ted M.; Rosenthal, Liana S.
Abstract: Background: In Parkinson's disease, the association between objective and patient-reported measures of cognitive dysfunction is unknown and highly relevant to research and clinical care. Objective: To determine which cognitive domain-specific Montreal Cognitive Assessment (MoCA) subscores are most strongly associated with patient-reported cognitive impairment on question 1 (Q1) of the Movement Disorders Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS). Methods: We analyzed data from 759 PD participants and 481 persons without PD with in a retrospective, cross sectional analysis using data from the NINDS Parkinson's Disease Biomarkers Program (PDBP), a longitudinal, multicenter biomarker study. The relationship between a patient-reported cognitive rating (MDS-UPDRS q1.1) and objective cognitive assessments (MoCA) was assessed using multinomial logistic regression modeling and the outcomes reported as conditional odds ratios (cOR's) representing the relative odds of a participant reporting cognitive impairment that is "slight" versus "normal" on MDS-UPDRSq1.1 for a one unit increase in a MoCA sub-score, adjusted for age and education. Results: In PD participants, changes in visuospatial-executive performance and memory had the most significant impact on subjective cognitive impairment. A 1-point increase in visuospatial-executive function decreased the chance of reporting a MDS-UPDRS Q1 score of "slight" versus "normal" by a factor of 0.686 (p < 0.001) and each 1 point improvement in delayed recall decreased the odds of reporting "slight" cognitive impairment by a factor of 0.836 (p < 0.001). Conclusions: Conversion from a PD patient's report of "normal" to "slight" cognitive impairment may be associated with changes in visuospatial-executive dysfunction and memory more than other cognitive domains. Highlights: Subjective and objective cognitive impairment in Parkinson's disease are compared. Early cognitive complaints associate with posterior cortical deficits in Parkinson's. Visuospatial deficits underlie early cognitive complaints in Parkinson's disease.